Freeze-Derived Anisotropic Porous Microparticles for Engineered Mesenchymal Stem Cell Loading and Wound Healing - Rongwei Cai; Shuangshuang Miao; Xinyue Cao; Min Nie; Yuanjin Zhao (Research)
Hydrogel microparticles that can effectively deliver mesenchymal stem cells (MSCs) are expected to accelerate wound repair progress. Attempts in the area are focusing on improving the functions of the microparticles and MSCs to promote the therapeutic effect. Here, inspired by the topological morphology of ice branches, we propose novel freeze-derived anisotropic porous microparticles for hepatocyte growth factor (HGF)-overexpressing MSCs (MSCsHGF) loading and wound healing. The microparticles were fabricated by introducing microfluidic methacrylated gelatin pre-gel droplets into low-temperature silicone oil, followed by photo-cross-linking and freeze-drying processes. Drawing an advantage from the biocompatible chemical composition and the structured pore arrangement of the microparticles, MSCsHGF can be efficiently encapsulated and released, maintaining continuous HGF secretion to enhance cell migration and support vascular regeneration. Leveraging these characteristics, we have shown that MSCsHGF-loaded porous microparticles could substantially promote angiogenesis, polarize macrophages toward the M2 phenotype, and reduce inflammation during the wound repair process, consequently enhancing skin wound repair efficiency. Thus, we believe that our MSCsHGF-integrated freeze-derived anisotropic porous microparticles hold promising prospects for clinical wound-healing applications.